Analisis pesan "video call dengan bu rika'' pada akun instragram @jokowi - Afsyah, Surahmad; Jusnita, Raden Ayu Erni (Soetomo Communication and Humanities, 2021)
right now video is already can not be apart of human life, at the begining video was only oriented in tv show but now it has many change of video and its a lot soround us. In this digital's era there are many kind of video as intention it created such as news video, education video, press release video, commercial advertazing video, society video, political campaign video and the other finnaly video reseachs are axist in comunicate study. Video with title Video call with Bu Rika at Instagram account @Jokowi is one of interesting video to do reseach this video is full dialog between Mr.Jokowi as president and Mrs.Rika as teacher from Padang. this video showing to viewer about education world in current condition while in pandemic start since first of 2020. Sign theory of ferdinand de saussure is matching theory to find out the meaning in this video.Â Keywords:Meaning; sign theory ; Ferdinand saussure